"You're not like other Malays": understanding the Singaporean Malay identity, its ethnicised discourses and the racial identification process - Nur Faeza Bte Mohamed Kefli (2018)
Singapore offered an interesting case to study race relations. In the public sphere, racial identities were highly regulated by its government via the Chinese-Malay-Indian-Other (CMIO) model. In the private sphere, the interpretation and articulation of racial identities beyond CMIO parameters were left to the individual’s discretion. In order to understand the relationship between structure and agency, the CMIO model was deconstructed beyond its practical implementations and analysed as a discourse. This exploratory study on educated Malays’ perceptions of their racial identities uncovered: 1) a ‘basic Malay identity’, 2) “ethnic thinking” and multiple ethnicised discourses, 3) ethnic-boundary negotiations with both the in-group and out-group, and 4) various racial identification strategies. It was found that the sample had to negotiate their Malay identity with their academic motivations and achievements in the presence of disparaging ethnicised discourses. Ethnic boundaries, which were supposed to be relinquished by multiculturalism and meritocracy, were erected when ethnicised discourses were imposed onto them, affecting how they negotiated their positions. As agents, they responded by adopting different stances and strategies, presenting varied expressions of ‘Malayness’.